Studi Fenomenologi Integrasi Biodiversity Accounting dalam Model Bisnis Keberlanjutan UMKM Madu Teuweul - Arianto, Bambang; Sari, Gema Ika (Jurnal Manajemen Strategis: Jurnal Mantra, 2025)
This study aims to analyze the integration of biodiversity accounting in the sustainability business model for Micro, Small, and Medium Enterprises (MSMEs) of Teuweul Honey. This is because preserving biodiversity in a business context can enhance business competitiveness. Thus, the concept of biodiversity accounting can be applied in the operations of MSMEs based on natural resource ecosystems. This study employs a phenomenological approach with the Interpretative Phenomenological Analysis (IPA) method. Data were obtained through in-depth interviews and observations with categories based on the statements of the research subjects. This study involved three subjects who were Teuweul Honey farmers in Serang Regency. The research subjects stated that the integration of biodiversity accounting in the sustainability business model of MSMEs of Teuweul Honey contributed to increasing profits in business management, preserving natural resource ecosystems, and biodiversity, and strengthening the added value of products. This study also found that there was an increase in transparency in reporting environmental and social impacts in the context of MSMEs which could be one of the strengthening of consumer preferences.